The investigator of pupils’ mathematical capabilities Romualdas Paliokas - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2009)
Mathematics teacher Romualdas Paliokas (1929–1977) worked Mol˙ etai, Ignalina and Anykščiai districts, the city of Panev˙ ežys. He investigated the pupils’ mathematical capabilities and prepared a doctoral thesis. Two major articles were published in pedagogical periodicals. He was unable to defend the thesis, because he died.
Keywords: doctoral thesis; mathematical capabilities; pupils; teacher of mathematics